2016
DOI: 10.1051/0004-6361/201527591
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum transport efficiency in post-main sequence low-mass stars

Abstract: Context. Using asteroseismic techniques, it has recently become possible to probe the internal rotation profile of low-mass (≈1.1−1.5 M ) subgiant and red giant stars. Under the assumption of local angular momentum conservation, the core contraction and envelope expansion occurring at the end of the main sequence would result in a much larger internal differential rotation than observed. This suggests that angular momentum redistribution must be taking place in the interior of these stars. Aims. We investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(112 citation statements)
references
References 57 publications
6
105
1
Order By: Relevance
“…The asteroseismic data obtained for the stellar core rotation from the mixed modes stochastically excited in sub-giants and red giants provide very good constraints for the transport of angular momentum in evolved stars (e.g. Beck et al 2012;Mosser et al 2012;Deheuvels et al 2012Deheuvels et al , 2014Deheuvels et al , 2015Spada et al 2016;Gehan et al 2018). The observed stars have masses ranging between 1.1 and 1.4 M .…”
Section: Case Of Red Giant Stars Illustrated With a 125 M Modelmentioning
confidence: 99%
“…The asteroseismic data obtained for the stellar core rotation from the mixed modes stochastically excited in sub-giants and red giants provide very good constraints for the transport of angular momentum in evolved stars (e.g. Beck et al 2012;Mosser et al 2012;Deheuvels et al 2012Deheuvels et al , 2014Deheuvels et al , 2015Spada et al 2016;Gehan et al 2018). The observed stars have masses ranging between 1.1 and 1.4 M .…”
Section: Case Of Red Giant Stars Illustrated With a 125 M Modelmentioning
confidence: 99%
“…The combination of space-based helio-and asteroseismology has demonstrated that stably stratified rotating stellar radiation zones are the seats of efficient transport of angular momentum throughout the evolution of stars. This strong transport leads to a uniform rotation in the case of the Sun down to 0.2 R (García et al 2007) and to weak differential rotation in other stars (e.g., Mosser et al 2012;Deheuvels et al 2012Deheuvels et al , 2014Kurtz et al 2014;Saio et al 2015;Murphy et al 2016;Spada et al 2016;Van Reeth et al 2016Aerts et al 2017;Gehan et al 2018;Ouazzani et al 2019). Four main mechanisms that transport angular momentum and mix chemicals are present in stellar radiation zones (e.g., Maeder 2009;Mathis 2013;Aerts et al 2019, and references therein): instabilities of the differential rotation (e.g., Zahn 1983Zahn , 1992, stable and unstable magnetic fields (e.g., Spruit 1999;Fuller et al 2019), internal gravity waves (e.g., Zahn et al 1997;Talon & Charbonnel 2005;Pinçon et al 2017), and largescale meridional circulations (e.g., Zahn 1992;Maeder & Zahn 1998;.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a ν add of 3 × 10 4 cm 2 s −1 as a mean value for the efficiency of the transport process, constrained strongly by the asteroseismic observations. Spada et al (2016) followed a similar approach to constrain the missing process by including a diffusive process to the transport of angular momentum that varies with the ratio of core to envelope rotation rate, inspired by the azimuthal magneto-rotational instability (AMRI, see Rüdiger et al 2007). They compare their stellar evolution models to observations of core rotation rate from Deheuvels et al (2014) and Mosser et al (2012) and conclude that the missing process of angular momentum transport has to change throughout the evolution of a star to be able to match the post-main sequence rotational evolution of lowmass stars.…”
Section: Introductionmentioning
confidence: 99%